The Popular Arts - Hall, Stuart, 1932-2014; Whannel, Paddy, 1922-1980 (Book collections on Project MUSE., 2018)
When it first appeared in 1964, Stuart Hall and Paddy Whannel's The Popular Arts opened up an almost unprecedented field of analysis and inquiry into contemporary popular culture. Counter to the prevailing views of the time, Hall and Whannel recognized popular culture's social importance and considered it worthy of serious study. In their analysis of everything from Westerns and the novels of Mickey Spillane, Ian Fleming, and Raymond Chandler to jazz, advertising, and the television industry, they were guided by the belief that studying popular culture demanded an ethical evaluation of the text and full attention to its properties. In so doing, they raised questions about the relation of culture to society and the politics of taste and judgment in ways that continue to shape cultural studies. Long out of print, this landmark text highlights the development of Hall's theoretical and methodological approach while adding a greater understanding of his work. This edition also includes a new introduction by Richard Dyer, who contextualizes The Popular Arts within the history of cultural studies and outlines its impact and enduring legacy.